Study on bonding mechanism of hot-cast anchorage of Galfan-coated steel cables. (1st November 2021) - Liu, Hongbo; Guo, Liulu; Chen, Zhihua; Meng, Yadan; Zhang, Yingjie
Highlights: The bonding performance and failure mechanism of hot casting anchor was studied. A partial-debonding model and the critical embedded length Lc were proposed. The pull-out tests at room and high temperature were carried out. The effects of different factors on bond strength were studied in this paper. A prediction formula of bond strength under fire was proposed. Abstract: As a common anchoring method of prestressed cable, hot cast anchor is lack of relevant research and complete design method. In engineering, safety is usually ensured by safety factor, resulting in material waste. In this paper, the bonding properties and failure mechanism between Galfan-coated steel wire and hot casting material at room temperature and high temperature were deeply studied. The following conclusions are obtained: 1) Based on the elastic shear lag model and the debonding theory, the stress transfer of the Galfan-coated steel wire–hot-cast material interface during the steel wire-drawing process was investigated, and a partial-debonding model and the calculation method of critical embedded length Lc were proposed; 2) The failure load and mechanism of steel wire with different anchorage length and insertion angle are obtained by pull-out test at room temperature. It is found that the bond strength of steel wire with Galfan-coated inserted vertically is 16 MPa, which is less than that of ordinary galvanized steel wire. 3) Carry out the pull-out test of steel wire at high temperature to obtain the failure mechanism of steel wire hot cast anchor under fire, and put forward the prediction formula of bond strength of hot cast anchor under fire, which provides theoretical basis for the design of hot cast anchor.